Exploring the Effects of Celery Stem on Blood Pressure, and Associated Parameters as Social Determinants in Hypertensive Individuals: A Randomized Control Trail - Zafar, Muhammad Umar; Rasheed, Amna; Ismail, Huda (Annals of Human and Social Sciences, 2023)
The aim of the current study was to investigate the medicinal effect of celery extract against the parameters of blood pressure, heart rate long with serum electrolyte levels of studied individuals. For this purpose, the celery stem extract was firstly analyses for its chemical and phenolic composition. Thirty Female human subjects chosen randomly from the society based on their history in the fluctuation of hypertensions were equally divided into two groups which was G0 as control group contained fifteen subjects and treatment group as G1 contained fifteen subjects. Treatment group-I was given encapsulated celery stem extract in doses of 250mg for the periods of two months. The treatment group showed significant reduction in systolic and diastolic blood pressure and associated parametrs . The most potent components of celery, A. graveolens, have consequently demonstrated hypolipidemic, and hypotensive effects. We outlined the processes behind celery component protection against insulin action, glucose, lipid metabolism, and blood pressure in the article.